Does the intensity of daily walking matter for protecting against the development of a slow gait speed in people with or at high risk of knee osteoarthritis? An observational study. Issue 9 (September 2018) - Fenton, S.A.M.; Neogi, T.; Dunlop, D.; Nevitt, M.; Doherty, M.; Duda, J.L.; Klocke, R.; Abhishek, A.; Rushton, A.; Zhang, W.; Lewis, C.E.; Torner, J.; et al.
Summary: Objective: Knee osteoarthritis (OA) is a risk factor for a decline in gait speed. Daily walking reduces the risk of developing slow gait speed and future persistent functional limitation. However, the protective role of walking intensity is unclear. We investigated the association of substituting time spent not walking, with walking at light and moderate-to-vigorous intensities for incident slow gait over 2-years, among people with or at high risk of knee OA. Method: We used baseline and 2-year follow-up data from the Multicenter Osteoarthritis (MOST) study ( n  = 1731) and the Osteoarthritis Initiative (OAI, n  = 1925). Daily walking intensity was objectively assessed using accelerometer-enabled devices, and classified as; not walking (<1 steps/min), very-light (1–49 steps/min), light (50–100 steps/min), and moderate-to-vigorous (>100 steps/min). We defined slow gait during a 20-m walk, as <1 m/s and <1.2 m/s. Isotemporal substitution evaluated time-substitution effects on incident slow gait outcomes at 2-years. Results: Replacing 20 min/day of not walking with walking at a moderate-to-vigorous intensity, demonstrated small to moderate reductions in the risk of developing a gait speed <1.0 m/s (Relative Risk [95% confidence interval (CI)]; MOST = 0.51 [0.27, 0.98], OAI = 0.21 [0.04, 0.98]), and <1.2 m/s (MOST = 0.73 [0.53, 1.00], OAI = 0.65 [0.36, 1.18]). However, only risk reductions for <1.0 m/s met statistical significance. Replacing not walking with very-light or light intensity walking was not associated with the risk of developing slow gait outcomes. Conclusion: When possible, walking at a moderate-to-vigorous intensity (>100 steps/min) may be best recommended in order to reduce the risk of developing critical slow gait speed among people with, or at high risk of knee OA.